Persaingan Bisnis: Telaah Konsep Pemikiran Kahrudin Yunus - Nuradi, Nuradi; Khatimah, Husnul; Wulan, Elis Ratna (Jurnal Ilmiah Ekonomi Islam, 2024)
This research discusses current business competition practices which tend to have a negative connotation, namely unhealthy competition and bringing each other down. The aim of the research is to provide an overview and paradigm regarding the true meaning of the word competition. In this research the researcher used a literature review method or literature review which focuses on collecting past data, especially the opinions of economic experts, in this case Kahrudin Yunus, who he wrote about in his book "Economic Systems According to Islam/Islamism volumes 1 and 2" the concept of business competition healthy". The results of the research found Kahrudin Yunus' views on the meaning of competition, an explanation of the positive benefits of competition, the initial causes of unhealthy competition and solutions to return to the initial concept of healthy competition. The implications of this research are expected to provide enlightenment and a new paradigm for all levels of society regarding the positive meaning of competition. And it is also important for all mankind to remember the purpose of its creation so that it can return to the rules set by the owner of the universe so that the meaning of "Bersamasime" can be realized.